Phraseological units of the thematic group “Leisure” in the aspect of translatability / untranslatability (on the material of the English and Ukrainian languages) - Krapyva, Yuliia; Medved, Olena (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
The ideas of O. Potebnia, whose scientific output is distinguished by a clear interest in the national peculiarities of the reality perception as well as the accumulation of culture of a certain ethnic group in its language, are fruitful for the study of the translatability / untranslatability of one language units into the other, in particular its phraseological units.The objective of the paper in question is to study phraseological units of the thematic group “Leisure” in English and Ukrainian, taking into account the issue of their translatability / untranslatability.The above-mentioned issue is related to the possibility to convey adequately the meaning encoded in the unit of the original by the means of the target language as well as to the degree of equivalence of the source and target units. While translating the specific class of units – phraseologisms, the possible difficulties can be overcome by using component analysis, which at the initial stage allows the translator to determine semantic components, as understanding them is necessary to select an adequate phraseological counterpart in the target language. The phraseologisms of the thematic group “Leisure” have the following common semantic components: cessation of work, the opportunity to relax and rest, recovery after fatigue.The research material is phraseological units selected from online resources dedicated to phraseologisms and idioms in English and Ukrainian. According to our observations, the phraseological units of the thematic group under study can be classified into two subgroups that are opposite in their approach to leisure: active pastime and passive pastime. It has been found out that the counterpart available in the target language is mostly a partial equivalent. Due to the difference in imagery, the loss of the idioethnic component of the phraseological unit is noticeable. As a result, there are no grounds to claim the untranslatability of the phraseological units of the thematic group in question. The possibility to convey the meaning encoded by the set expressions of the English and Ukrainian languages is due to the common components in the meaning of the lexeme “leisure” in the consciousness of the speakers of both languages.Further research can be devoted to the analysis of the ways of translating phraseological units of the thematic group “Leisure”, which were used by specialists during the translation of fiction.